Optimal choice method of practical gateway cloud access to storage - Струбицький, Р. П.; Найда, О. М. (Problems of Informatization and Control, 2015)
To build a cloud storage data systems of access to and security practices necessary choosing theoptimal gateway access. Most of the access to the cloud storage gateway do not make a choice, anduse standard gateway. This reduces the speed and quality of customer service and significantly affectsthe security of data transmitted through cloud storage. There are practical approaches make itimpossible to solve this problem. Developed the method of choosing the best practical gateway accessto data storage in two versions. The method makes it possible to create a more flexible and quickaccess to data warehousing in which optimality is determined dynamically, which is important tomobile subscribers